Chemical and botanical analysis of the Lavender sample commercialized in the Ver o Peso market. (Research, Society and Development, 2022)
Lavandula sp. is popularly known as lavender, it belongs to the Lamiaceae family, presenting important properties used in the pharmaceutical, cosmetic and medicinal industries, such as: antifungal, bactericidal, pain reduction and treatment of skin diseases. However, another genus is also popularly marketed as lavender. The tests carried out in the laboratory of the Centro Universitário Fibra aimed to evaluate the botanical and phytochemical profile of the extracts prepared from the branches and leaves of the sample, aiming at an organographic characterization and preliminary research of the secondary metabolites present in it. The species used in the tests was acquired at the Ver o Peso market, located in the Belém city of state Pará, in February 2022. To obtain the hydroalcoholic extract, the leaves and branches were macerated for about 7 days, already to obtaining the soft extract, part of the initial extract was placed in the desiccator for about 7 days, the results were evaluated according to the methods described by the Brazilian Society of Pharmacognosy. In the extract, the presence of the following metabolites were identified: tannins, saponins, catechins and alkaloids. From the botanical identification and phytochemical analysis it was possible to conclude that it was not the genus Lavandula sp. and yes of the genus Aloysia sp.